2020
DOI: 10.1080/21678421.2020.1813780
|View full text |Cite
|
Sign up to set email alerts
|

Who cares for the bereaved? A national survey of family caregivers of people with motor neurone disease

Abstract: Background: Although Motor Neurone Disease (MND) caregivers are most challenged physically and psychologically, there is a paucity of population-based research to investigate the impact of bereavement, unmet needs, range of supports and their helpfulness as perceived by bereaved MND caregivers.Methods: An anonymous national population-based cross-sectional postal and online survey of bereavement experiences of family caregivers who lost a relative/friend to MND in 2016MND in , 2017MND in , and 2018. Recruitm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 46 publications
1
29
0
Order By: Relevance
“… 5 However, at least three times as many families stay grappling with grief following this traumatic experience, many of them agonising over what could have worked better. 7 Notwithstanding the physical, psychological and emotional burden of the disease on MND family caregivers, the Deloitte Access Economic Report 8 has quantified the economic disadvantage on families supporting people with MND in Australia. These caregivers provide an estimate of 7.5 h of informal care per day with the productivity loss estimated at $68.5 million in 2015, or $32,728 per person, with families shouldering most of these costs ($44.0 million) and with government bearing the rest ($24.5 million) in the form of lost taxes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“… 5 However, at least three times as many families stay grappling with grief following this traumatic experience, many of them agonising over what could have worked better. 7 Notwithstanding the physical, psychological and emotional burden of the disease on MND family caregivers, the Deloitte Access Economic Report 8 has quantified the economic disadvantage on families supporting people with MND in Australia. These caregivers provide an estimate of 7.5 h of informal care per day with the productivity loss estimated at $68.5 million in 2015, or $32,728 per person, with families shouldering most of these costs ($44.0 million) and with government bearing the rest ($24.5 million) in the form of lost taxes.…”
Section: Introductionmentioning
confidence: 99%
“…A majority of participants (63%) required bereavement support beyond their family and social networks. 7 Most had accessed support from family and friends, followed by MND Associations, general practitioners (GPs) and funeral providers. While informal supports were considered the most helpful, sources of professional help were the least used and were perceived to be the least helpful.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This intervention contains communication skills tools to help externalize the problem and set realistic goals (Malkinson, 2010). Among them, guiding and reassuring the person to reduce anxiety symptoms and explore emotions (Aoun et al, 2020;Morris et al, 2020); transmitting therapeutic support to process information and recognize emotion (Neimeyer, 2014); paying attention to self-care; maintenance of social relationships through the internet, mobile, etc. ; help to restructure thinking; expressing and identifying emotions; recognizing positive emotions (Lyubomirsky, 2008).…”
Section: Relapse Prevention Plan Cognitive Behavioral Therapy and Behavioral Activationmentioning
confidence: 99%
“…On other hand, self-applied interventions appear as an option to arrive at a great number of participants. To make a selfapplied intervention effective, tools are included to communicate skills that help to externalize the problem and set realistic goals, as recommended by Malkinson (2010), with the crosscutting objective of reducing anxiety symptoms and exploring emotions (Aoun et al, 2020;Morris et al, 2020). Along the same lines, previous research has shown the effectiveness of online tools in grief support that help improve the adaptive adjustment of people in grief (Dominick et al, 2010).…”
Section: Introduction Backgroundmentioning
confidence: 99%